Diabetes evolution in rats after neonatal treatment with alloxan - Ribeiro, Carla [UNESP]; De Oliveira, Camila Aparecida Machado [UNESP]; Luciano, Eliete [UNESP]; De Mello, Maria Alice Rostom [UNESP] (My University, 2005)
Physical exercises have been recommended in the prevention of non-insulin dependent diabetes mellitus (NIDDM), but the mechanisms involved in this intervention are not yet fully understood. Experimental models offer the opportunity for the study of this matter. The present study was designed to analyze the diabetes evolution in rats submitted to neonatal treatment with alloxan with the objective of verifying the suitability of the model to future studies with exercises. For this, newly born rats (6 days old) received intraperitoneal alloxan (A= 200 mg/kg of body weight). Rats injected with vehicle (citrate buffer) were used as controls (C). The fasting blood glucose level (mg/dL) was higher in the alloxan group at the day 28 (C=47.25 ± 5.08; A=54.51 ± 7.03) but not at the 60 day of age (C=69.18 ± 8.31; A=66.81 ± 6.08). The alloxan group presented higher blood glucose level during glucose tolerance test (GTT) (mg/dL. 120 min) in relation to the control group both at day 28 (C=16908.9 ± 1078.8; A=21737,7 ± 1106.4) and at day 60 (C=11463.45 ± 655.30; A=15282.21 ± 1221.84). Insulinaemia during GTT (ng/mL.120 min) was lower at day 28 (C=158.67 ± 33.34; A=123.90 ± 19.80), but presented no difference at day 60 (C=118.83 ± 26.02; A=97.88 ± 10.88). At day 60, the glycogen concentration in the soleus muscle (mg/100mg) was lower in the alloxan group (0.3 ± 0.13) in relation to the control group (0.5 ± 0.07). No difference was observed between groups in relation to (μmol/g.h): Glucose Uptake (C= 5.8 ± 0.63; A= 5.2 ± 0.73); Glucose Oxidation (C= 4.3 ± 1.13; A= 3.9± 0.44); Glycogen Synthesis (C= 0.8± 0.18; A= 0.7 ± 0.18) and Lactate Production (C= 3.8± 0.8; A= 3.8± 0.7) by the isolated soleus muscle. The glucose-stimulated insulin secretion (16.7mM) by the isolated islets (ng/5 islets, h) of the alloxan group was lower (14.3± 4.7) than the control group (32.0± 7.9). Thus, we may conclude that this neonatal diabetes induction model gathers interesting characteristics and may be useful for further studies on the role of the exercise in the diabetes mellitus appearance. Copyright © 2005 by PJD Publications Limited.
Keywords: Alloxan; Diabetes mellitus; Neonatal treatment; Rats